Trusted Communications with Physical Layer Security for 5G and Beyond - Duong, Trung Q.; Zhou, Xiangyun; Poor, H. Vincent (IET telecommunications series ;, 2017)
Securely transferring confidential information over a wireless network is a challenging task. This book addresses security issues, not only for 5G but also beyond, using physical layer security technology and techniques.